A 4D tensor-enhanced multi-dimensional convolutional neural network for accurate prediction of protein–ligand binding affinity - Dingfang Huang; Yu Wang; Yiming Sun; Wenhao Ji; Qing Zhang; Yunya Jiang; Haodi Qiu; Haichun Liu; Tao Lu; Xian Wei; Yadong Chen; Yanmin Zhang (Molecular Diversity, 2025)

Characterization and Phylogenetic Analysis of the Complete Mitochondrial Genome of white-spotted Bamboo Shark (Chiloscyllium plagiosum) - Dingfang Lu; Xiaowen Huang; Ruirui Zhao; Xiaoyan Xie; Shanshan Cai (Thalassas: An International Journal of Marine Sciences, 2024)

Multimodal multi-task deep neural network framework for kinase–target prediction - Yi Hua; Lin Luo; Haodi Qiu; Dingfang Huang; Yang Zhao; Haichun Liu; Tao Lu; Yadong Chen; Yanmin Zhang; Yulei Jiang (Molecular Diversity, 2023)

Genomic Comparison and Genetic Marker Identification of the White-Spotted Bamboo Shark Chiloscyllium plagiosum - Ruirui Zhao; Shanshan Cai; Dingfang Lu; Pengfei Li; Shengyong Xu; Yuan Li (Frontiers in Marine Science, 2022)
The white-spotted bamboo shark ( Chiloscyllium plagiosum ) is an ecologically and commercially important marine cartilaginous fish in the Indo-Western Pacific. However, the resources of this species are declining in recent years due to habitat degradation and overfishing. Studies on genomics and genetic markers can provide valuable information for sound management and conservation of C. plagiosum . In this study, genome resequencing data of a domesticated C. plagiosum individual were generated for genomic comparison between wild and domesticated samples. Based on 281.17 Gb of clean sequencing data, the genome size of the domesticated sample was estimated as 4.99 Gb, with heterozygosity of 0.51% and repeat ratio of 74.67%, which is about 1 Gb larger than that of the wild sample (3.85 Gb with a repeat ratio of 63.53%). By using a reference-based approach, we assembled a nearly 3.45 Gb genome sequence of the domesticated sample, with the scaffold N50 of 69.45 Mb. Subsequent identification of genome-wide microsatellite markers confirmed the different abundance of repeat elements in wild and domesticated C. plagiosum . Additionally, a total of 8,703,211 single-nucleotide polymorphisms (SNPs) were detected and annotated. The demographic analysis based on identified SNPs revealed a large and constant effective population size of C. plagiosum after the last population expansion (~0.3 million years ago). The genomic data and identified genetic markers in this study can provide fundamental and useful information for further comparative genomics, evolutionary biology, and conservation genetics of C. plagiosum .